Qualidade da semeadura e do arranquio mecanizado do amendoim - Zerbato, Cristiano [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The successful deployment and digging peanut depends on the soil condition, the mechanized systems and the quality of agricultural operations indexes. The quality of seeding is essential to obtain adequate plant population seeking high yields and in the digging should be done in the best possible conditions to prevent the pods losses. Furthermore, the use of automatic routing technology has been used for the purpose of improving alignment and efficiency of operations. In this work three studies were carried out to evaluate the quality of sowing (first study) and digging (second study) peanut mechanized in three different textural classes of soils (Sandy, Clayey and Silty) and water content conditions that they were, beyond comparison of operations carried out using the autopilot or manually operated (third study). The experiments were performed in locations of São Paulo, Brazil, in a completely randomized design, arranged in bands, and used statistical process control to evaluate the quality of operations. In the first study the highest quality obtained for seeding density and normal spacing gave the soil of Clay textural class an initial stand of seedlings and more homogeneous as expected. The Sandy had only their quality affected by greater variability obtained due to water soil conditions at planting. Already Silty textural class, except the density and sowing depth that is unique of machine performance, obtained lower quality than other soil types due to harmful conditions on the soil water content and rainfall. In the second study, the homogeneity of the conditions of the water contents found at the time of digging on Silty textural class of soil resulted in lower losses and process variation, resulting in a higher quality. The Clay textural class had lower quality that soil Silty for only differences in variability, but not disqualified. The Sandy showed soil water content and pods out of the ideals and stipulated standards ...

O êxito da implantação e do arranquio de amendoim depende da condição dos solos, dos sistemas mecanizados e dos índices de qualidade das operações agrícolas. A qualidade da semeadura é imprescindível para se obter uma população adequada de plantas visando altas produtividades e o arranquio deve ser realizado nas melhores condições possíveis para se evitar as perdas de vagens. Além disso, a utilização da tecnologia de direcionamento automático tem sido utilizada com a finalidade de melhorar o paralelismo e eficiência das operações. Neste trabalho foram realizados três estudos que tiveram como objetivos avaliar a qualidade da semeadura (primeiro estudo) e do arranquio (segundo estudo) mecanizados de amendoim em três solos de classes texturais distintas (arenosa, média e argilosa) e as condições de teor de água que os mesmos se encontravam, além da comparação das operações realizadas com o uso do piloto automático ou operadas manualmente (terceiro estudo). Os experimentos foram realizados em localidades do estado de São Paulo, Brasil, sob delineamento inteiramente casualizado, dispostos em faixas, e utilizado o controle estatístico de processos para avaliar a qualidade das operações. No primeiro estudo a maior qualidade obtida para densidade de semeadura e espaçamentos normais conferiu ao solo da classe textural Argilosa um estande inicial de plântulas mais homogêneo e dentro do esperado. A Arenosa somente teve sua qualidade afetada pela maior variabilidade obtida devido às condições hídricas do solo no momento da semeadura. Já a classe textural Média, com exceção à densidade e profundidade de semeadura que é exclusivo do desempenho da máquina, obteve qualidade inferior aos demais tipos de solo devido às condições prejudiciais quanto ao teor de água do solo e às precipitações pluviais. No segundo estudo, a homogeneidade das condições dos teores de água encontrada no momento do...
Keywords: Amendoim; Controle de processo - Métodos estatísticos; Máquinas agrícolas; Mecanização agrícola; Semeadeira-adubadeira; Drills (Planting machinery)